Komposit poliester/serat gelas: pengaruh jumlah lapisan serat terhadap sifat mekaniknya - Suardana, NPG; Surata, IW (Jurnal Energi Dan Manufaktur; Vol 2, No.1 Juni 2007, 2012)
Technology of polymers and composites progressively expand which had been found of various new composite types with excellence and also it’s excess. Currently, one of the composite materials was used in many industrial of automotive as vehicle body especially for components that needed light material with high strength and high corrosive resistance is Glass Fiber Reinforced Polymer (GFRP). This research investigated whether the addition of fiber layer can increase flexural strength of the composite, and how many the maximum fiber layer or maximum fiber fraction of weight. The experiment used unsaturated polyester Resin type of Yukalac 157 BQTN-EX as matrix, short glass fiber sheet with random orientation (chopped random mat) type of MAT 300 as reinforcement, and methyl etil keton peroxide (MEKPO) as hardener, respectively. The specimens were made by press hand lay-up and then formed and underwent the flexural testing according to standard of ASTM D 790 - 03. From the result and data analysis, it can be concluded that the weight fraction and fiber volume fraction increased with fiber layer. These resulted in the increase of flexural modulus and strength of GFRP. The specific strength and specific flexural modulus had relatively constant value, because the increase of flexural strength will be followed by increased its density. The number of maximum fiber layer in 1 mmcomposite in thickness was 3 layers (MAT 300), which approached the maximum fiber fraction of weight (Wf = 58.69%, 60% maximum).
Keywords: Polymer composite, fibreglass, flexural strength, flexural modulus, strain